Weed Biology and Control - Pilipavičius, Vytautas (IntechOpen, 2015)
This book is a collection of chapters, concerning the developments within the Weed Biology and Control field of study. The book includes scholarly contributions by various authors pertinent to Agricultural and Biological Sciences. Each contribution comes as a separate chapter complete in itself but directly related to the book's topics and objectives. The target audience comprises scholars and specialists in the field.